Yesus Kristus Sebagai Perwujudan Hikmat Allah: Sebuah Tafsiran Teologis Terhadap Yakobus 3:13-18 - Winarjo, Hendra (Veritas : Jurnal Teologi dan Pelayanan, 2023)
From the time of the Reformation until contemporary times, the epistle of James has been considered to have no significant contribution to Christian theology. When compared to Paul's letters, the letter of James is less desirable or even often considered inferior to be involved in theological discourse. In reality, it can be argued that James 3:13-18 provides constructive theological implications when read with a theological interpretation of Scripture approach. This article proposes an assessment with a theological interpretation approach to James 3:13-18 to see the Christological indication that Jesus Christ is the embodiment of God’s wisdom. Without neglecting the importance of the praxis of wisdom, this interpretation theologically testifies that the gentle, from above, pure, reconciling, gracious, obedient, merciful and so on wisdom that James refers to has been realized in and through the person of Jesus Christ. The church as a community of believers who read James 3:13-18 needs to realize its calling to become a community of wise people with the power of the Holy Spirit to imitate the life of Jesus who is the embodiment of God's wisdom.